Pemberdayaan Kelompok Wanita Tani Melalui Participatory Rural Appraisal (PRA) di Kelurahan Battang Kota Palopo - Wahyuni Husain; Bahtiar; Muhammad Ashabul Kahfi (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2020)
The participation of women in the farming family in helping the families welfare is very important, especially farmer women's group in Battang Urban Village, Palopo City. This service activity aims to empower farmer wives who are members of the women farmer groups to help their families' welfare through the PRA (Participatory Rural Appraisal) method. The method was directed at strengthening the capacity of KWT Mandiri members in the Battang Village, Palopo City to prepare their plans, funding, schedules, take action, and carry out monitoring and evaluation. Through this method, the farmer's wife who is part of a woman farmer group can help their family's welfare by selling ornamental plants. This service activity can be said to be successful because the farming family becomes more prosperous and empowered.